Tackling potentially inappropriate prescriptions in older adults: development of deprescribing criteria by consensus from experts in Colombia, Argentina, and Spain - Roxana De las salas; Claudia Vaca-González; Javier Eslava-Schmalbach; Catalina Torres-Espinosa; Albert Figueras (BMC Geriatrics, 2023)
Abstract Background Potentially inappropriate medication use is prevalent among older adults in primary care, leading to increased morbidity, adverse drug reactions, hospitalizations, and mortality. This study aimed to develop and validate a tool for identifying PIMs in older adults within the primary care setting. The tool is composed of a list of criteria and was created based on consensus among experts from three Spanish-speaking countries, including two from Latin America. Methods A literature review was conducted to identify existing tools, and prescription patterns were evaluated in a cohort of 36,111 older adults. An electronic Delphi method, consisting of two rounds, was used to reach a formal expert consensus. The panel included 18 experts from Spain, Colombia, and Argentina. The content validity index, validity of each content item, and Kappa Fleiss statistical measure were used to establish reliability. Results Round one did not yield a consensus, but a definitive consensus was reached in round two. The resulting tool consisted of a list of 5 general recommendations per disease, along with 33 criteria related to potential problems, recommendations, and alternative therapeutic options. The overall content validity of the tool was 0.87, with a Kappa value of 0.69 (95% CI 0.64—0.73; Substantial). Conclusions The developed criteria provide a novel list that allows for a comprehensive approach to pharmacotherapy in older adults, intending to reduce inappropriate medication use, ineffective treatments, prophylactic therapies, and treatments with an unfavorable risk–benefit ratio for the given condition. Further studies are necessary to evaluate the impact of these criteria on health outcomes.